(untitled) - Temple, Juno; 1989-; Semler, Dean; Riley, Sam; 1980-; Howard, James Newton; 1943-; Copley, Sharlto; Freeman, Gary; Pearson, Richard; (Film editor); Lebenzon, Chris; et al. ([Burbank, California], 2014)
A beautiful, pure-hearted young fairy, Maleficent has an idyllic life growing up in a peaceable forest kingdom, until one day when an invading army threatens the harmony of the land. Bent on revenge, Maleficent faces a battle with the invading kings successor and, as a result, places a curse upon his newborn infant Aurora. As the child grows, Maleficent realizes that Aurora holds the key to peace in the kingdom, and perhaps to Maleficents true happiness as well. A retelling of the Sleeping Beauty story.
Keywords: United States; Film adaptations; Sleeping Beauty (Tale); Feature films; Blessing and cursing; Drama; Princesses; Drama; Childrens films; Action and adventure films; Fantasy films